Design and Development of ALU using Multi Chiplet Methodology for High-Performance Computing - Amrita Rai; Owais Ahmad Shah; Imran Ahmed Khan; Mubeen Ahmad Khan; Latika Jindal; Piyush Chouhan (Buletin Ilmiah Sarjana Teknik Elektro, 2026)
The fundamental programmable logic unit (PLU) in any microprocessors or a microcontrollers and real-time processor of integrated circuits is the arithmetic and logical unit (ALU). The conventional ALUs had exorbitant power consumptions, route delays, and transistor counts because they were created using complementary metal oxide semiconductor (CMOS) technology. Therefore, the motivation of this paper is on the design and development of ALU using Multi Chiplet design Methodology with FPGA kit and simulation is perform on vivado software. Multi-Chiplet systems helps reduce the cost of chip design, low power consumption and increases yield for complicated SoCs (System on Chips). Low power with less design space semiconductors will be the future of computing as the power requirements and size of the SoC cannot be expanded above the set limit. There is a need to reconsider how the design ALU to shorten the time needed for their development as designer continue to push the current limit boundaries of the present CMOS process. This paper proposed a Multi Chiplet SoC structure of ALU with low power, less area required and in small packaging for mostly used in CPU of all type computing devices. The basic function of ALU is to perform arithmetic and Logic operations, required multiplication and additions. In this paper booth multiplier and Kogee-Stone Adder are proposed with multi-chip module (MCM) for low power consumption, less area requirement, high processing speed and less delay. Due to the ever-growing requirements of increasing the Floating-Point Operations per Second (FLOPs) of the processing unit in the field of high-performance computing and AI, there needs to be changes in both the overall design and also the design methodology in fabricating an ALU.